Core Set of Patient-reported Outcomes in Pancreatic Cancer (COPRAC): An International Delphi Study Among Patients and Health Care Providers. Issue 1 (July 2019) - van Rijssen, Lennart B.; Gerritsen, Arja; Henselmans, Inge; Sprangers, Mirjam A.; Jacobs, Marc; Bassi, Claudio; Busch, Olivier R.; Fernández-Del Castillo, Carlos; Fong, Zhi Ven; He, Jin; Jang, Jin-Young; Javed, Ammar A.; et al.
Abstract : Objective: To establish an international core set of patient-reported outcomes (PROs) selected by both patients and healthcare providers (HCPs) from the United States (US), Europe, and Asia. Summary Background Data: PROs are increasingly recognized in pancreatic cancer studies. There is no consensus on which of the many available PROs are most important. Methods: A multicenter Delphi study among patients with pancreatic cancer (curative- and palliative-setting) and HCPs in 6 pancreatic centers in the US (Baltimore, Boston), Europe (Amsterdam, Verona), and Asia (Mumbai, Seoul) was performed. In round 1, participants rated the importance of 56 PROs on a 1 to 9 Likert scale. PROs rated as very important (scores 7–9) by the majority (≥80%) of curative- and/or palliative-patients as well as HCPs were included in the core set. PROs not fulfilling these criteria were presented again in round 2, together with feedback on individual and group ratings. Remaining PROs were ranked based on the importance ratings. Results: In total 731 patients and HCPs were invited, 501 completed round 1, and 420 completed both rounds. This included 204 patients in curative-setting, 74 patients in palliative-setting, and 142 HCPs. After 2 rounds, 8 PROs were included in the core set: general quality of life, general health, physical ability, ability to work/do usual activities, fear of recurrence, satisfaction with services/care organization, abdominal complaints, and relationship with partner/family. Conclusions: This international Delphi study among patients and HCPs established a core set of PROs in pancreatic cancer, which should facilitate the design of future pancreatic cancer trials and outcomes research. Abstract : Supplemental Digital Content is available in the text